1993
DOI: 10.1111/j.1365-2249.1993.tb05954.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of interferon-gamma in hyperplastic lymph nodes from HIV-infected patients

Abstract: SUMMARY Polyclonal B cell activation is characteristic of HIV infection and occurs in the presence of severe CD4+ lymphocyte depletion. In contrast, CD4+ lymphocytes are the dominant T cell in the reactive lymphoid tissues of patients not infected with HIV. In this study, lymph node biopsies from eight HIV‐infectcd patients with persistent generalized lymphadenopathy syndrome (PGL) were assessed for IL‐lβ, IL‐2, IL‐4, IL‐6, IL‐10, interferon‐gamma (IFN‐γ) and tumour necrosis factor‐beta (TNF‐β) gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…T lymphocytes from HIV-infected patients express [37,38] and secrete [39] IFN--, at an increased rate, but are unable to produce iL-4 [39]. In this regard it is of interest thai both cyiokines modulating CD14 derive from different subsets of T helper cells, IFN-7 from Thl and IL-4 from Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T lymphocytes from HIV-infected patients express [37,38] and secrete [39] IFN--, at an increased rate, but are unable to produce iL-4 [39]. In this regard it is of interest thai both cyiokines modulating CD14 derive from different subsets of T helper cells, IFN-7 from Thl and IL-4 from Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of membrane-bound CDi4 and release of soluble CD14 by monocytes is down-regulated by T cellderived IL-4 and interferon-gamma (IFN-7) [35,36]. T lymphocytes from HIV-infected patients express [37,38] and secrete [39] IFN--, at an increased rate, but are unable to produce iL-4 [39]. In this regard it is of interest thai both cyiokines modulating CD14 derive from different subsets of T helper cells, IFN-7 from Thl and IL-4 from Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients were also shown to have high levels of HIV antigenreactive Th I -like cells which, upon recognition of HIV recombinant antigens, responded by secretion of IFN-y (Lolli et al, manuscript submitted). IFN-y was also found in brain autopsy specimens [12] and over-expressed in lymph nodes from HIVinfected patients [13]. Elevated serum levels ofTGF-)?…”
Section: Introductionmentioning
confidence: 91%
“…Tfh cells have been shown to express high levels of IL-6R that correlated with increased IL-6 levels during chronic SIV infection 61 . Recent studies have implicated IFNγ as a potential mechanism for the accumulation of Tfh in the GC 71 and Boyle et al 72 showed that IFN γ levels were significantly enhanced in the LN of HIV infected patients. Expansion of Tfh cells have been reported in a number of autoimmune diseases such as SLE 73 , Sjogren’s syndrome 74 , Rheumatoid Arthritis 75 and Juvenile Dermatomyositis 20 .…”
Section: Hiv Infection and Tfh Cellsmentioning
confidence: 99%